WATERMARKING PADA CITRA DIGITAL MENGGUNAKAN KOMBINASI PIXEL VALUE INDICATOR DAN METODE MOST SIGNIFICANT BIT - Lumbanraja, Posma (Universitas Methodist Indonesia, 2019)
One way to protect the copyright and authenticity of a digital image is to affix a watermark in the form of writing or a sign on the image. If the affixed watermark is visible, then its presence can interfere with the appearance of the image and it is possible that the watermark will be cut, discarded, or cropped by parties who are not entitled to do so. In this paper, an application is designed to affix a watermark in the form of an invisible message, or an invisible watermark by using a combination of pixel value indicator and the Most Significant Bit (MSB) method on the image, so that it is not detected visually and the visual appearance of the image is not disturbed. The message is scrambled using a key, then the scrambled bits are hidden in the 5th bit MSB and the 6th bit of the green channel or blue channel, depending on the number of bits 1 owned by the red channel which serves as an indicator. The process of hiding the watermark is carried out in the middle area of ​​the image, so it is difficult to cut to remove it. Applications designed can be used to affix an invisible watermark in the form of messages that are not easily removed on digital images, so that they can protect the copyright of a digital image.